2017
DOI: 10.1016/j.jvs.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of abdominal aortic aneurysm progression by oral administration of green tea polyphenol in a rat model

Abstract: EGCG attenuated AAA progression in a rat model by preserving the aortic thickness and elastin content of the medial layer through regeneration of elastin, as mediated by anti-inflammatory effects, and subsequent reduction of matrix metalloproteinase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In previous studies, many dietary components or herbal extracts such as advanced glycation end products (AGEs), copper, green tea, vitamin D, β-carotene, vitamin B6, Calendula officinalis have been shown to regulate LOX activity [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. AGEs are a group of reactive compounds formed by the Maillard reaction.…”
Section: Dietary Components Regulate Lox Activitymentioning
confidence: 99%
“…In previous studies, many dietary components or herbal extracts such as advanced glycation end products (AGEs), copper, green tea, vitamin D, β-carotene, vitamin B6, Calendula officinalis have been shown to regulate LOX activity [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. AGEs are a group of reactive compounds formed by the Maillard reaction.…”
Section: Dietary Components Regulate Lox Activitymentioning
confidence: 99%
“…Several scientific studies have shown that tea contains high levels of antioxidant polyphenols, such as flavonoids and catechins [19][20][21][22][23]. These polyphenolic compounds can eliminate the dangerous free radicals such as superoxide anion radicals (O 2 •), hydrogen peroxide (H 2 O 2 •), and hydroxyl radicals (HO•), thereby preventing the progression of various diseases such as cancers [24,25] (e.g., prostate gland cancer [26], lung cancer [27]), osteoporosis [28], cardiovascular diseases [29] and Parkinson's disease [30], abdominal aortic aneurysm [31].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that polyphenols such as pentagalloyl glucose (PGG) and Epigallocatechin gallate (EGCG) can increase elastin deposition by smooth muscle cells derived from healthy or aneurysmal rat aorta [4]. Others have shown than in an elastase model of AAA, a high dose of grape seed polyphenol used orally has a protective role for elastin, and decrease immune cells and MMPs at the AAA site [5]. Green tea polyphenol EGCG was used orally to a rat model of abdominal aortic aneurysm induced by intraluminal infusion of elastase and adventitial simultaneous CaCl 2 application where EGCG prevented the progression of AAA [5].…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown than in an elastase model of AAA, a high dose of grape seed polyphenol used orally has a protective role for elastin, and decrease immune cells and MMPs at the AAA site [5]. Green tea polyphenol EGCG was used orally to a rat model of abdominal aortic aneurysm induced by intraluminal infusion of elastase and adventitial simultaneous CaCl 2 application where EGCG prevented the progression of AAA [5]. These studies used excessively high oral doses of polyphenols at the onset of AAA induction and showed an only protective effect.…”
Section: Introductionmentioning
confidence: 99%